Both The Folate Therapy and the Folate Treatment Combined with Zinc Had an Effect on the Endocrine Markers and Sperm Characteristics of Sub-Fertile Males - Shakeeb Ahmed, Muhammad Ubaid, Muhammad Babar Baig, Adeel Bashir, Rafat Rasheed, Zeeshan Aslam (Pakistan Journal of Medical & Health Sciences, 2022)
Aim: The purpose of this study was to see how folate and folate + zinc treatment affected endocrine markers and sperm properties in sub fertile males. Methods: The methodical research in addition meta-analysis was carried out. From 1969 to May 2020, databases were searched by Medline, Scopus, Google scholar, and Persian databases have been examined that used the set of pertinent keywords comprising "folate or folic acid AND (infertility, infertile, sterile)". Any standardized clinical studies that took oral folic acid or folate plus zinc on a selection of sub fertile males for semen analysis are included in the. Endocrine characteristics and sperm parameters were among the information gathered. Comprehensive Meta-analysis Version 2 was used for data methods. Results: Eight researches remained comprised in the total. Seven researches have enough information for a meta-analysis. "Sperm concentration was significantly greater in males treated using folate than in men not supplied using folate (P.002)." Furthermore, folate supplementation unaided did not appear to remain additional beneficial than the placebo in terms of sperm morphology (P =.057) or motility (P =.653). In comparison to the placebo, folate with dietary supplementation had no measurable difference in blood testosterone (P =.87), inhibin B (P =.85), FSH (P =.056), or sperm motility (P =.168). However, as given a placebo, folate with zinc had a substantially bigger influence on semen parameters (P.002), morphology (P.002), and blood folate level (P.002). Conclusion: Folate and zinc supplementation improves sperm qualities in infertile men. Nonetheless, because of the significant heterogeneity of the papers used in this meta-analysis, those findings must be regarded with care. More research is necessary to corroborate the existing results. Keywords: Effect of Folate, Folate Plus Zinc Supplementation, sperm properties, sub fertile males.